Variability of Arctic Sea ice age and its relationship with atmospheric circulation patterns - Chen, Ping; Wang, Xiaoyu; Zhao, Jinping; Li, Tao; Shi, Junqiang; Zong, Fangyi; Wei, Lai (Frontiers in Marine Science, 2023)
Since at least the 1990s, global warming has caused the decline of multi-year ice (MYI) in the Arctic, which has made the Arctic Ocean more susceptible to the effects of climate change and weather processes. In this study, an analysis of the variations in Arctic sea ice age was carried out based on the results of an Empirical Orthogonal Function (EOF) analysis. Variations in three time periods were investigated. The first period (1984-1995) is characterized by high sea ice age, with antiphase variation processes in the eastern and western parts of the Arctic Ocean. The second period (1996-2012) represents a rapid reduction in ice age, characterized by a gradual replacement of MYI in the Arctic Ocean with seasonal sea ice, resulting in a decreased extent of MYI. The third period (2013-2022) is characterized by low sea ice age, with ice age being in a significantly negative phase. Furthermore, trend-like changes were weak during this period. During the first period, the spatial distribution and significant variations in ice age were driven by cyclonic wind anomalies associated with the Arctic Oscillation (AO) atmospheric pressure modes. The cyclonic wind fields in winter and anticyclonic wind fields in summer collectively influenced the sea ice. This led to a decrease/increase in ice age in the eastern/western Arctic, and antiphase variations were apparent. During the second study period, winter ice age variations were driven by cyclonic wind anomalies associated with the AO atmospheric pressure modes, leading to ice divergence and a decrease in ice age. In summer, both thermodynamic (Arctic warming) and dynamic (DA) mechanisms play a role in modulating the changes of sea ice age, while Arctic warming is the primary driver. The DA generated anomalous wind patterns, characterized by the Beaufort Gyre and Transpolar Drift, which resulted in the outflow of MYI from the Arctic under the influence of meridional winds. During the third study period, the influence of AO/DA and air temperature on sea ice age changes is greatly weakened.